KARAKTERISASI KERAGAMAN GENETIK POPULASI JABON PUTIH MENGGUNAKAN PENANDA RANDOM AMPLIFIED POLYMORPHISM DNA - ILG Nurtjahtjaningsih; Maryatul Qiptiyah; Tri Pamungkas Yudohartono; AYPBC Widyatmoko; Anto Rimbawanto (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2014)
Anthocepalus cadamba (white jabon) has high economical value for furniture. White jabon forests severely degraded due to intensive exploitation and land conversion. Genetic diversity is one of important consideration to design conservation and improvement strategies. Aim of this study was to access the genetic diversity values within and among population of white jabon. Leaf samples of white jabon were collected from conservation plots originated from West Lombok, Sumbawa, South Sumatera and West Sumatera. Red jabon was included as an outgroup population. Based on 37 polymorphic RAPD loci, the results showed comparable value of genetic diversity between white jabon and red jabon. Number of detected and rare alleles was highest founded in Sumbawa population among the other three populations of white jabon. As consequence, value of expected heterozygosity in the population was highest (HE=0.315). Private allele was only detected in South Sumatera population. Principal coordinate analysis (PCA) showed that integrating between genetic and geographical distance was inconsistent; similar gene resources or human impact might be responsible for this result. The populations that have high value of genetic diversity and private allele are recommended to be selected for the conservation strategies, i.e. Sumbawa and South Sumatera.